2017
DOI: 10.7754/clin.lab.2017.161107
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum TARC, TSLP and POSTN Levels and Childhood Atopic Dermatitis

Abstract: Serum POSTN, TARC, and TSLP were higher in children with atopic dermatitis. Serum TARC and TSLP levels might be used as biomarkers to predict severe atopic dermatitis and serum POSTN to predict atopy and disease chronicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
2
16
1
1
Order By: Relevance
“…Kou et al [20] detected higher levels of serum periostin in patients with erythrodermic type AD and widespread type AD, as compared to patients with lesions that had not spread systemically. Uysal et al reported significant correlations between plasma periostin levels and the duration of symptoms and the presence of atopy [21]. Our results contrast with these study results, and this difference may be associated with sample sizes, recruitment strategies and ELISA kit-specific changes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Kou et al [20] detected higher levels of serum periostin in patients with erythrodermic type AD and widespread type AD, as compared to patients with lesions that had not spread systemically. Uysal et al reported significant correlations between plasma periostin levels and the duration of symptoms and the presence of atopy [21]. Our results contrast with these study results, and this difference may be associated with sample sizes, recruitment strategies and ELISA kit-specific changes.…”
Section: Discussioncontrasting
confidence: 99%
“…Various biomarkers such as TARC, TSLP, IL-31, and IL-33 have been investigated to evaluate the pathogenesis of AD and to predict severity and chronicity. TARC and TLSP were found to be related to AD severity and chronicity [21]. Our study has some limitations.…”
Section: Discussionmentioning
confidence: 93%
“…However, few studies have attempted to investigate how osteoblasts initiate osteoclasts aggregation and differentiation, promote the formation of the eruption channel, or explored whether autophagy occurs during this process. Periostin (POSTN) is a multifunctional soluble intercellular matrix protein that is mainly expressed in the periosteum and regulates osteoblasts to increase value, differentiation, and adherence (Uysal et al, 2017;Zeng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As an epithelium-derived cytokine, TSLP activates dendritic cells to induce a Th2 response, resulting in the production of Th2 cytokines, such as IL-4 and IL-13 [26]. TARC and TSLP are highly expressed in serum and AD lesions, leading to Th2-mediated allergic inflammation in the development of AD [27,28]. This study showed that the secretion levels of RANTES, TARC, and TSLP were dose-dependently reduced by NHGR treatment in TNF-α and IFN-γ-induced HaCaT cells.…”
Section: Discussionmentioning
confidence: 99%